Thursday

August 21, 2014

August 21, 2014

Posted by **Ben** on Monday, July 23, 2007 at 10:24am.

Hint: Think of a simple problem like f(x) = x + 3. Then the inverse, h(x) would be h(x) = x - 3. What would the composition f[h(x)] equal in this example?

f(h) means the function operates on h.

f(h)= h+3= x-3+3=x

Notice that

h(f)= f-3=x=3-3=x

**Related Questions**

Calculus - F(x) = 1-x and g(x) = 1/x These functions have the property that f = ...

Algebra 2 - Find the inverse of the following function: f(x) = 3x + 12 I don't ...

inverse - find f^-1 (x). (this is asking me to find the inverse) f(x) = -(x-2)^2...

Algebra - I have to solve an inverse function. f(x)=x+6 and g(x)=x+6 f(x)=1/4x,x...

Calculus (Please check my work!) - Suppose that y = f(x) = x^2 - 4x + 4. Then on...

algebra 2 - for each function, find an equasion for the inverse. then use ...

algebra 2 - for each function, find an equasion for the inverse. then use ...

algebra 2 - for each function, find an equasion for the inverse. then use ...

Algebra 2 - so i got a question and would like to know if i did this right For ...

algebra - Can someone help with inverse relations and functions? is relation t a...